Integrated Microcentrifuge Carbon Entrapped Glucose Oxidase Poly (N-Isopropylacrylamide) (pNIPAm) Microgels for Glucose Amperometric Detection. (24th March 2019) - Mugo, Samuel M.; Berg, Darren; Bharath, G.
Abstract: This study demonstrates a miniaturized integrated glucose biosensor based on a carbon microbeads entrapped by glucose oxidase (GOx) immobilized on poly (N-isopropylacrylamide) (pNIPAm) microgels. Determined by the Lowry protein assay, the pNIPAm microgel possesses a high enzyme loading capacity of 31 mg/g. The pNIPAm GOx loaded on the microgel was found to maintain a high activity of approximately 0.140 U determined using the 4-aminoantipyrine colorimetric method. The integrated microelectrochemical cell was constructed using a microcentrifuge vial housing packed with (1:1, w/w) carbon entrapped by pNIPAm GOx microgels, which played the dual role of the microbioreactor and the working electrode. The microcentrifuge vial cover was used as a miniaturized reference electrode and an auxiliary electrode holder. The device can work as biosensor, effectively converting glucose to H2 O2, with subsequent amperometric detection at an applied potential of −0.4 V. The microelectrochemical biosensor was used to detect glucose in wide linear range from 30 µM to 8.0 mM, a low detection limit of 10 µM, a good linear regression coefficient ( R 2 ) of 0.994, and a calibration sensitivity of 0.0388 µA/mM. The surface coverage of active GOx, electron transfer rate constant (ks), and Michaelis–Menten constant ( K M app ) of the immobilized GOx were 4.0 × 10 −11  mol/cm 2, 5.4 s −1, and 0.086 mM, respectively. To demonstrate the applicability and robustness of the biosensor for analysis of high sample matrix environment, glucose was analyzed in root beer. The microelectrochemical device was demonstrated for analysis of small sample (<50 µL), while affording high precision and fast signal measurement (≤5 s).